Waste to energy plant in Spain: A case study using technoeconomic analysis - Medina-Mijangos, Rubí; Contelles-Rodríguez, Sergi; Guerrero-García-Rojas, Hilda R.; Seguí-Amórtegui, Luis (Waste-to-Energy: Recent Developments and Future Perspectives towards Circular Economy, 2023)
Home Waste-to-Energy Chapter Waste to Energy Plant in Spain: A Case Study Using Technoeconomic Analysis Rubí Medina-Mijangos, Sergi Contelles-Rodríguez, Hilda Guerrero-García-Rojas & Luis Seguí-Amórtegui Chapter First Online: 08 February 2022 1015 Accesses Abstract The population growth and the new consumption models contribute significantly to a greater generation of waste, which is generally incorrectly managed because a large percentage of the waste generated is sent to landfills. Waste to energy (WtE) plants play a fundamental role in managing and treating municipal waste because they reduce the amount of waste sent to landfills and reduce dependence on imported fossil fuels; however, these facilities can also cause negative impacts. This case study evaluates the technical–economic feasibility of an incineration plant by using a social cost–benefit analysis, which considers economic, social, and environmental impacts taking into account the 3 pillars of sustainability and allowing policymakers to have a complete view of the impacts generated by the facility. The WtE facility is in Barcelona (Spain). It produces energy from municipal solid waste (MSW) with a total capacity of more than 350,000 tons of waste treated per year, which means the generation of more than 180,000 MWh of electricity and 110,000 tons of steam per year. The positive and negative impacts generated by this facility are identified, discussed, and monetarily valued to carry out this economic analysis. Some of the impacts considered are the sale of energy, the decrease in waste disposal in landfills, the reduction of greenhouse gas (GHG) emissions, and the generation of dioxin emissions. The results show that the facility is profitable from a private point of view (BP = 15.97) and an economic, environmental, and social perspective (BT = 37.48). Finally, the same impacts can be considered by researchers in future economic analyzes of other WtE projects or waste management systems.
Keywords: case study; environmental impacts; MSW; social impacts; technical-economic analysis; waste to energy; Scopus(2)